HEALTH EDUCATION PROGRAM EVALUATION ON HEALTHY LIVING WITHOUT DRUGS AND FREE SEX OF SENIOR HIGH SCHOOL STUDENTS IN INSTITUTION X TANGERANG - Maria Susila Sumartiningsih; Theresia -; Dora Samaria (Universitas Pelita Harapan, 2017)
Background of Community Service activities on health education is to provide understanding for senior high school students who are in the age range of adolescents. In the adolescent age group tend to have an unstable personality, very susceptible to negative environmental impact, drug use, and free sex behavior. Health education is a preventive action that needs to be done by various parties to fight against drug use and free sex among adolescents. The purpose of this evaluation is to get constructive feedback from students to improve the quality of the implementation of community service for the next period. Evaluation of the implementation of community service was distributed to the students through the existing evaluation form. The evaluation instrument consists of seven statements using a Likert scale. This scale consists of five options of answers with a score range of 1-5, which is very satisfied (score 5), satisfied (score 4), quite satisfied (score 3), dissatisfied (score 2), very dissatisfied (score 1). The population of activity evaluation was 133 senior high school students at Institution X in Tangerang, sample took by total sampling technique. Data analysis was used univariate analysis. Evaluation of the process of community service activity was obtained the result that time and place of execution can be executed according the plan, but the target numbers were exceed target, that was initially only first grade student only, then become increasing grade 2 and 3 because the material is important, so the total number of participants became 133 students. The evaluation of the process of community service activity is focused on the students' perception on the content of the activity material, which consists of seven components: the conformity of the topic / material with the needs, material conformity and the purpose of counseling, the benefit of the topic / material for the participants, the achievement of the target of the extension program, the efficiency of the use of extension time, and the method of delivery of extension materials used. The results of the assessment of the seven components are between 84.4% - 96.6% (satisfied - very satisfied). It can be concluded that the activity of community service is running well.